Manajemen kultur sekolah dalam upaya peningkatan mutu pendidikan di SMA Negeri 2 Brebes - Evi Rovikoh Indah Saputri; Samsi Haryanto (Universitas Sarjanawiyata Tamansiswa, 2016)
The study aims to investigate all information about the management of the school culture including the achievement culture, characteristic, and extracurricular activity in SMA Negeri 2 Brebes in terms of election and development of school culture, conviction and assumption of school culture, target of development school culture, planning, organizing, implementing, observing, producing the schoolculture. This study was conducted the qualitative research approach. The research subjects included the headmaster, vice-headmaster, teachers, and students. The data were collected by observing, interviewing, and documenting. The data were analyzed by reducing, presenting, and summarizing the data. The research finding showed that the management of the school culture in the effort of improving educational quality in SMA Negeri 2 Brebes by developing achievement culture, characteristic, extracurricular activity to improve the schools’willingness, the student’s potential, teachers’ potential, and schools’ facilities was an effort developing the school culture. The target development of achievement culture was gaining the conviction the schools’ member of SMA 2 Brebes to be able to produce students to have some achievements and be proud. The target of characteristic culture was equalizing the achievement culture. The target of extracurricular activity was producing the students’ achievement in the non-academic area. The planning of culture development accommodates the planning of students’ affair program, and facilities. The organization, in general, was implemented by determining the structure of organization by details of duty, the responsibility of organizational element as the development of the schools’ culture authority. The implementation of achievement culture was conducted by academic and non- academic competition, participation in the competition, and effective learnings. The implementation of character culture was conducted by applying 18 scores of the characteristic of the schools’ member and activities. The implementation of extracurricular activity covered the obligation and optional activity. The observation was conducted by collecting information both formal and informal dialogs, observing students’ attitudes and behaviors, observing the students’ achievement. The school culture product was included by having planned, implementing, reporting and resulting.